#### Answer

1) Factoring
2) Quadratic Formula
3) Completing the square

#### Work Step by Step

The 3 ways to solve a quadratic equation are
1) Factoring
$$x^{2}+4x+4$$ $$(x+2)(x+2)$$
2) Quadratic Formula
$$\frac{-b+/-\sqrt (b^{2}-4(ac))}{2a}$$
3) Completing the Square
$$x^{2}+12x+32=0$$ $$x^{2}+12x=-32$$
Now you take the b which is 12 divide by 2 and square it.
$(\frac{12}{2})^{2}=36$
The result add it on both sides to keep the balance.
$$x^{2}+12x+36=-32+36$$ $$x^{2}+12x+36=4$$
Now factor it.
$$(x+6)(x+6)=4$$
$$\sqrt (x+6)^{2}=\sqrt 4$$
Now we will divide this into two negative and positive.
$(x+6)=2$ and $(x+6)=-2$
$x=-4 and x=-8$